RegTech: Case Study Of Its Implementation In the Financial Industry - Zou, Jiacheng (Transactions on Economics, Business and Management Research, 2024)
Regulators are emphasizing the importance of data governance to support more frequent reporting cycle. It aids industry stakeholders in fulfilling their regulatory governance, reporting, and compliance responsibilities while managing risk. The goal of RegTech is to prioritize and improve the effectiveness of regulations and governance while reducing the cost of compliance through the application of various new technological solutions. Data security, regular updates and customer privacy are the main challenges for RegTech to solve. Over these years, it is still an emergent implementation in many industries and will be facilitated in more financial fields.